Effect of growing conditions on seed yield and quality of cucumber (Cucumis stivus) hybrid - KADDI, GIRISH; B S, TOMAR; SINGH, BALRAJ; KUMAR, SANJAY (The Indian Journal of Agricultural Sciences, 2014)
The present investigation was carried out at Centre for Protected Cultivation Technology (CPCT) farm at Indian Agricultural Research Institute (IARI), New Delhi during summer and kharif seasons 2011 under naturally ventilated polyhouse, insect proof net house and open field conditions to study the influence of different growing conditions on seed yield and quality of cucumber (Cucumis sativus) hybrid (Cv Pant Shankar Khira 1) seed production. The seed parent and pollen parent were grown in 3:1 ratio. Water and nutrients were provided through drip fertigation in all three conditions. In all three growing conditions, vine length and number of leaf nodes were significantly more in kharif season compared to summer season. Number of fruit developed to maturity was significantly more in kharif (2.15) than summer (1.90). The vine length, number of leaves, fruit weight, fruit length and fruit width were significantly higher under naturally ventilated polyhouse and insect proof net house compared to open field in both of the seasons. The number of seeds/fruit was significantly higher in insect proof net house (204.15) and naturally ventilated polyhouse (188.35) as compared to open condition (126.05). The seed yield/fruit, seed yield/plant and seed yield per 1000 m2 were significantly higher in kharif season as compared to summer. Whereas higher seed yield was recorded in insect proof net house followed by naturally ventilated polyhouse and open field condition. The seed quality attributes, viz. germination percentage, seedling length, seedling dry weight, vigour index I and II and seed moisture content immediately after harvest were also significantly superior in naturally ventilated polyhouse and insect proof net house in comparison to open field conditions. The benefit-cost ratio (BCR) is higher in insect proof net house (1:2.25) followed by open condition (1:1.12) naturally ventilated polyhouse (1:0.37).